Pelatihan Electronic Workbench (EWB) Dalam Pembelajaran Fisika Bagi Siswa/i di SMA Citra Harapan Percut - Siti Nurhabibah Hutagalung; Anda Yanny; Sumiaty Adelina Hutabarat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In Physics subjects, so far the students have learned, among others, electronic coupling and the introduction of electronic components without any visual simulation with special media or electronic software. The availability of supporting learning media that minimally inhibits the creation of effective learning activities. To overcome the lack of availability of laboratory equipment in Citra Harapan High School Percut Sei Tuan especially in experiments with dynamic electric circuits, software called Electronic Workbench 5.12 was used which was developed in the form of a simulation. With the existence of service activities carried out, it is expected that students are able to understand electronic design, capable of assembling simple electronic components using EWB.